2006
DOI: 10.1111/j.1399-0012.2006.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hepatitis and lamivudine therapy in 11 HBsAg‐positive renal allograft recipients: a single centre experience

Abstract: For HBsAg (+) renal allograft recipients, careful monitoring of HBV-DNA levels and timely administration of lamivudine could prevent hepatic damage caused by reactivation of hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…For many viral infections, such as HBV or EBV, resolution of illness is likely mediated by cellular immune responses that provide long‐term host control of viremia rather than viral eradication 33, 34. In HBV infection, it has been shown that virus‐specific cellular immunity contributes to self‐limited disease35 and that suppression of this immune control by chemotherapy or immune suppressive treatment can lead to viral reactivation 17–19. Thus, immune suppressive treatment following solid organ transplantation may place the individual at considerable risk of viral reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many viral infections, such as HBV or EBV, resolution of illness is likely mediated by cellular immune responses that provide long‐term host control of viremia rather than viral eradication 33, 34. In HBV infection, it has been shown that virus‐specific cellular immunity contributes to self‐limited disease35 and that suppression of this immune control by chemotherapy or immune suppressive treatment can lead to viral reactivation 17–19. Thus, immune suppressive treatment following solid organ transplantation may place the individual at considerable risk of viral reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients with chronic HBV infection (CHB) show generally weak and narrowly directed virus‐specific cellular immunity that may be functionally impaired 10–13. The initiation of Lamivudine therapy in these subjects has been shown to at least transiently increase clusters of differentiation (CD)4 and CD8 T cell–mediated immune responses against the HBV envelope (HBV surface antigen [HBsAg]) and nucleocapsid antigens (HBV core antigen)14–16 Comparably little is known about the role of the virus‐specific T‐cell responses in the OLT setting, although a deeper understanding of host immunity to HBV in OLT could facilitate the development of novel therapeutic immune interventions 17–19. The present study was thus designed to investigate the HBV‐specific cellular immune response in immune‐suppressed patients (OLT recipients) compared to patients with CHB (viremic and nonviremic) and self‐limited HBV infection.…”
mentioning
confidence: 99%
“…We thought that, this may be due to the spesifications of the patient group and may be a result of administring antiviral treatment to all patients. Viral reactivation usually develops in 1st year after transplantation (9,(31)(32)(33). Usage of higher doses of immunosuppressive drugs after Rtx in the 1st year is the major cause of this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are not likely to be generalizable to other disease states because of potentially unique rates and timing of HBV reactivation. Future studies should explore the costs and effectiveness of HBV prophylaxis in different disease states such as hepatocellular carcinoma, 46 breast cancer, 47 nasopharyngeal carcinoma, 48 rheumatologic diseases, 49 renal transplants, 50 lung transplants, 51 and inflammatory bowel diseases. 52 In our model, the prophylactic use of lamivudine was associated with 171 fewer HBV reactivations and 28 fewer overall deaths.…”
Section: Discussionmentioning
confidence: 99%